Approaches Toward Building the Digital Enterprise and Sustainable Economic Development: The Moderating Role of Sustainability - Pei, Jianhua (Frontiers in Psychology, 2022)
Achieving enduring economic development is the biggest challenge of today’s humanity. However, at present, there is a consensus that the digital economy plays a significant role in achieving sustainable economic development. The advancement of the digital enterprise is critical for obtaining socioeconomic stability and growth. In explanation, this study focuses on gaining economic progression through deploying the modern concept of digitalization. The study analyzes the mediating relationship of digital enterprise among e-commerce, digitalization, and digital marketing and their effect on China’s economic development while considering sustainability as a moderating variable. The study has used primary data collection techniques, and the study sample size is 400 respondents. The research has used SmartPLS software to measure the relationship through bootstrapping and algorithms. The study has found significant positive mediation of digital enterprise and moderation of sustainability between digital enterprise and economic development. This study suggests the theoretical and practical implications toward political stability, policymakers, and researcher perspective.